Spiradenoma: A Case Report and Review of the Literature - Jia-Ying Chang; Yen-Chang Chen; Dah-Ching Ding (Diagnostics)
Background and Clinical Significance: Spiradenoma is a rare benign skin adnexal tumor with unknown incidence and prevalence, typically affecting young to middle-aged adults without a sexual predilection. Case Presentation: A 59-year-old woman presented with a palpable lesion in the suprapubic region that had been there for 20 years and had become enlarged over the past 2 months. Physical examination revealed a firm, non-tender, subcutaneous mass, approximately 2 cm in size, in the right pubic region. Ultrasound revealed a hypoechoic, heterogeneous lesion with a well-defined border, measuring 2.37 × 0.94 × 1.67 cm, without hypervascularity. Therefore, the patient underwent excision of the subcutaneous tumor. The pathology report confirmed the diagnosis of spiradenoma of the pubis. Histochemistry showed that the inner luminal cells were positive for CK7, and the outer basaloid cells were positive for p63. CD56 and CD117 were focally positive. Conclusions: With an accurate diagnosis and appropriate surgical excision, the prognosis for spiradenoma is generally excellent. However, a long-term follow-up is advisable.